Evaluation of CCB-preserved medium density particleboards under natural weathering - Poleto, Sabrina Fernanda Sartório; de Moura Aquino, Vinicius Borges; Chahud, Eduardo; Pinheiro, Roberto Vasconcelos; Nunes Branco, Luiz Antonio Melgaço; Silva, Diogo Aparecido Lopes; de Campos, Cristiane Inácio [UNESP]; Molina, Julio Cesar [UNESP]; de Carvalho, Carlos Maviael; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (BioResources, 2020)
Wood engineered products are alternatives to the use of timber for civil construction, manufacturing, and the furniture industry. One of these products is the medium density particleboard (MDP) panel, which is made of wood particles and resin under high temperature and pressure. This research produced a prototype to evaluate the use of MDP panels waterproofed by castor oil-based polyurethane resin and Pinus sp. residues treated with CCB preservative for use as a wall coating. The influence of weathering, position of wood panel, and waterproof treatment were evaluated. Panels were made under the requisites of Brazilian Standard ABNT NBR 14810 (2013) and evaluated with international standards. MDP panels met standard requisites, with properties similar to that reported in the literature, indicating the possibility of use as wall coating. Statistical analysis indicated the only significant factor was weathering, which influenced physical and mechanical properties.
Keywords: Castor-oil resin; Medium density particleboard; Pinus sp.; Waterproofing; Weathering